Terrecotte votive da Taranto. Un tentativo di contestualizzazione di materiali sequestrati - Irene Managlia (Les Carnets de l’ACoSt)
The amount of votive terracottas yielded by ritual contexts in Magna Graecia have been increased by seized archaeological objects which have yet lost part of their informative power. The fragmentary statuettes presented here have been seized in 1979 and mainly consist in female heads dated from Archaism to Hellenistic Age. Stylistic an technical studies carried out in 2021–2022 revealed that our fragments strongly resemble the terracottas from Taranto and the types were comparable with those uncovered in some ritual contexts of the city. Our heads may have been removed from one or more of the votive deposits uncovered at Spring’s Sanctuary of Saturo currently interpreted as evidence of an abandonment rite.